Nursi’s Unity Model and Its Importance in the Context of Racial Unity in Malaysia - Mohamad Zaidin, Mat @ Mohamad; Ab. Aziz, Sulaiman; Azhar, Yaacob (Mediterranean Centre of Social and Educational Research, 2014)
Universal peace and prosperity is a humanitarian issue that has found a place in the thoughts of Badiuzzaman Said Nursi. His thoughts, which are pivoted on the al-Qur’an, traverse the boundaries of race and land. This article discusses the thoughts of Nursi that are inclined towards the values that reinforce cooperation between races and strategies that can be utilized in efforts to ensure the success of national integration in Malaysia. This study employed a qualitative approach based on primary and secondary sources through the method of document analysis. This article has found that the efforts need to focus on three main values, which are wasatiyyah (moderation), dialogue and nurturing virtuous values. Besides that, this article suggests a few strategic plans such as forming the Wasatiyyah Institute, consolidating the centre for dialogue on civilization and courses on dialogue skills and nurturing virtuous values through Islamic mass media.